The Effect of Basic Life Support Training on Knowledge about Handling Cardiac Arrest Victims in Destana Volunteers in Klotok Village, Plumpang District, Tuban - Tiara Putri Ryandini; Mokhamad Nurhadi (Alliance oh Health Activists (AloHA), 2021)
Cardiac arrest is a condition in which there is a sudden cessation of the normal circulation of blood characterized by a loss of arterial blood pressure. Cardiac arrest can be caused by cardiovascular disease factors or by accident factors. Cardiac arrest can happen anywhere and anytime, and many people around are not able to provide help if there are victims of cardiac arrest, so if there are victims, they are left alone. The purpose of this study was to determine the effect of basic life support training on knowledge of handling cardiac arrest victims in Destana volunteers in Klotok Village, Plumpang District, Tuban. The research method used is a cross sectional study approach. The population used in this study was Destana volunteers who met the inclusion criteria as many as 40, with a sample size of 36 respondents who were determined using simple random sampling. The independent variable in this study was basic life support training, while the dependent variable was the treatment of cardiac arrest victims. The instruments used in data collection are questionnaires and SOPs. Research analysis using Wilcoxon test. Statistical results showed that the basic life support training variable had a significant effect on the treatment of cardiac arrest victims with p-value = 0.002. The results of this study are suggested to be a reference for respondents, health institutions, the community and further researchers in increasing knowledge of handling cardiac arrest. Keywords: cardiac arrest; basic life support; Destana volunteers